2013
DOI: 10.1007/s10096-013-1970-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of virulence genes, 16S rRNA methylases, and plasmid-mediated quinolone resistance genes in CTX-M-producing Escherichia coli from Pakistan

Abstract: The aim of the study was to conduct a comprehensive molecular characterization of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli collected from Pakistan. Genetic relatedness among 98 ESBL-producing E. coli was measured by pulsed-field gel electrophoresis (PFGE). The presence of genes encoding ESBLs, virulence factors (VFs), 16S rRNA methylases, plasmid-mediated quinolone resistance (PMQR) encoding elements, plasmid replicon types, phylogenetic groups of E. coli, prevalence of the worldwide dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…E. coli ST131 strains are mostly of serotype O25:H4, with a specific O25 type, O25b. However, ST131 E. coli isolates of serotype O16:H5 have recently been identified in Japan, Denmark, Australia, Spain, Pakistan, and France (18)(19)(20)(21)(22)(23)(24). Moreover, some E. coli ST131 isolates have been shown to be nontypeable for O or H antigens (18,25).…”
Section: Bacterial Characteristicsmentioning
confidence: 99%
“…E. coli ST131 strains are mostly of serotype O25:H4, with a specific O25 type, O25b. However, ST131 E. coli isolates of serotype O16:H5 have recently been identified in Japan, Denmark, Australia, Spain, Pakistan, and France (18)(19)(20)(21)(22)(23)(24). Moreover, some E. coli ST131 isolates have been shown to be nontypeable for O or H antigens (18,25).…”
Section: Bacterial Characteristicsmentioning
confidence: 99%
“…A multicountry study reported that carbapenems are the treatment of choice for infections caused by ESBL-producing K. pneumoniae (26). Coresistance to several antimicrobial agents has often been described for CTX-M-producing isolates (27,28). These arrays of resistance genes confer a multidrug resistance phenotype that can be transferred horizontally (28).…”
Section: Discussionmentioning
confidence: 99%
“…Coresistance to several antimicrobial agents has often been described for CTX-M-producing isolates (27,28). These arrays of resistance genes confer a multidrug resistance phenotype that can be transferred horizontally (28). Integrons are mobile genetic elements that can be located either on a chromo-some or a plasmid and can integrate antibiotic resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Further exploration of antibacterial resistance of all ESBLs producing isolates against different antibacterial agents were done by using disc diffusion method [9]. Antibiotics used for disc diffusion method were amikacin (30 μg), colistin sulphate (10 μg), fosfomycin (50 μg), ciprofloxacin (10 μg), ceftazidime (30 μg), cefotaxime (30 μg), gentamicin (10 μg), imipenem (10 μg), nalidixic acid (30 μg), piperacillin-tazobactam (100 μg + 10 μg), trimethoprimsulfamethoxazole (1.25 μg + 23.75 μg) and ticarcillin-clavulanic acid (75 μg + 10 μg).…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Rapid emergence of ESBLs producing E. coli has been reported in a recent study from Pakistan [9]. Acquisition of multidrug resistance to commonly prescribed drugs leads scientists to introduce alternatives of these drugs that could be more potent for treatment of such infections and pathogens.Plants produce many secondary metabolites that have been familiar for biological activities [10].…”
Section: Introductionmentioning
confidence: 99%